Base genética de las arritmias primarias hereditarias más frecuentes: síndrome de QT largo, el síndrome de brugada y taquicardia ventricular polimórfica catecolaminérgica - Campos J., Danitza; Pardo V., Rosa (Revista Hospital Clínico Universidad de Chile, 2024)
Inherited primary arrhythmias correspond to a group of genetic disorders, including long QT syndrome (LQTS), Brugada syndrome (BrS), and catecholaminergic polymorphic ventricular tachycardia (CPVT), among others. They are usually caused by pathogenic variants in genes related to ion channels, predisposing to arrhythmias and cardiac events. Inherited primary arrhythmias affect approximately 1 in 3,000 people and are an important cause of sudden cardiac death, mainly in young adults. Diagnosis is based on clinical history, particular electrocardiographic patterns, and detection of mutations. Given that mutation carriers are usually diagnosed after presenting a cardiac event and that the consequences of not identifying or treating them promptly can be fatal, genetic studies are very relevant to guide management, define prognosis, and detect asymptomatic individuals in the family, after performing cascade genetic studies, which allows early intervention in this risk group. This article reviews the genetic causes of LQTS, BrS, and CPVT, highlighting the relevance of genetic studies in patients with these arrhythmias.